Neural tissues and chondrostean traits in a Carboniferous actinopterygian - Abigail M. Caron; Kristen Tietjen; Michael I. Coates (Proceedings of the National Academy of Sciences, 2026)
Ray-finned fishes (Actinopterygii) represent over half of extant vertebrate species, but their early evolutionary history is largely unresolved. Current phylogenetic estimates, corroborated by discoveries of preserved neural tissues, place most Palaeozoic actinopterygians outside the crown group and leave the deep roots of major extant divisions depauperate. Moreover, apparent fossil brains in early fishes are minuscule relative to endocranial chamber space, implying that endocasts are poor indicators of neuroanatomical gross morphology. Here, through X-ray micro-computed tomography of the early actinopterygian Trawdenia planti, we show unexpected neurocranial and neural soft tissue morphology indicative of a large brain fitting snugly within the endocranium. We find internal ventricular structures, present a model of neural tissue preservation, identify neuroanatomical characters, and demonstrate that endocasts capture phylogenetically and ecologically informative signal. These data suggest that Trawdenia bridges the gap between early actinopterygians and modern Chondrostei, thereby offering an alternative framework for understanding early actinopterygian neural evolution that departs radically from current phylogenetic hypotheses.